ANALISA BREAK EVEN POINT SOFA MINIMALIS PADA USAHA SOFA GALI PUAN DI KOTA AMBON - Abdullah Sombalatu; Febiola Matuankotta; Sherly Rutumalessy (P3M Politeknik Negeri Ambon, 2026)
Sofa Gali Puan is a business engaged in sofa furniture, which produces minimalist sofas to be sold to consumers and marketed to the public. So far, the amount of profit obtained is not known for sure. Because until now the Sofa Gali Puan business has never calculated the Break Even Point to plan their business profits in the coming period. The purpose of this study is to analyze the production of Minimalist Sofas in achieving Break Even PointIn this study, a quantitative analysis method was used, namely the calculation of break even points in units and rupiah. The results of the research obtained are Break Even Point in the number of units for minimalist sofas in the Gali Puan Sofa Business is 68 sets of minimalist sofas. Break Even Point in rupiah is at Rp.370,555,555.55The conclusion of this writing is that the Gali Puan Business will be at the break-even point or main return point when producing minimalist sofas of 68 sets at a cost of Rp.370,555,555.55. That means that the company is at break-even at that point, so the company doesn't experience any profits or losses. Thus, for the Gali Puan sofa business, it must continue to calculate the Break Even Point to find out what level of sales must be achieved which has an impact on the achievement of profits in the future. Keywords: Break Even Point (BEP)